(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This article examines the feasibility, methodology, and prognosis of laparoscopic surgery in the treatment of endometrioid cysts. The study emphasizes the advantages of laparoscopy, including minimal invasiveness, faster recovery, and lower recurrence rates compared to traditional surgical methods. The analysis also focuses on the selection of optimal surgical techniques based on cyst size, localization, and reproductive plans of patients. The outcomes demonstrate that laparoscopy remains the most effective and safe approach in managing endometrioid ovarian cysts, contributing to the preservation of ovarian function and improving reproductive health.